2020
DOI: 10.21037/cdt.2020.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical versus transcatheter aortic valve replacement for patients with aortic stenosis at low-intermediate risk

Abstract: Background: To compare safety and efficacy of transcatheter aortic valve replacement (TAVR) with surgical aortic valve replacement (SAVR) in patients at low-intermediate risk, given the paucity of robust data. Methods:We performed an aggregate data meta-analysis of 7 randomized controlled trials (RCTs) and 6,778 patients comparing TAVR with SAVR for aortic stenosis (AS) in low-intermediate risk patients (Society of Thoracic Surgeons risk-score ≤8%) using the random-effects model. Primary outcome was allcause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… References 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 …”
Section: Supporting Informationunclassified
“…Contrary to the transfemoral approach, patients undergoing transapical TAVR require a pericardiotomy and several studies have shown that pericardial injury can lead to postoperative inflammation and the subsequent development of POAF. Furthermore, meta-analyses of RCTs 30 for patients at low and intermediate surgical risk showed a significant risk reduction for POAF using TAVR compared with SAVR. This finding is to be expected since an open procedure is associated with more postoperative inflammation, enhanced sympathetic stimulation and oxidative stress as opposed to a minimally invasive procedure such as TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to other recently published meta-analyses. [29][30][31][32] From our analysis, we note the tremendous advances to the treatment of AS with the advent of TAVR. The similar outcomes of TAVR and SAVR at 5 years in data from 2 randomized trials of low-and intermediate-risk patients is reassuring for the efficacy of TAVR in mid-term follow-up.…”
Section: Discussionmentioning
confidence: 99%